Membangun Karakter AUD dalam Pengembangan Nilai Agama dan Moral di RA Masyithoh Pabelan Kab. Semarang - Sabi'ati, Amin (Al-Athfal: Jurnal Pendidikan Anak, 2016)
This article is intended to reveal the importance of character building of children through the development of religious and moral values ​​in early childhood in RA Masyithoh Pabelan Semarang regency, the factors that influence the character building, the process of the development of moral and religious values, behavioral changes, and its implementation in the system for early childhood learning. The results showed that the learning that emphasizes hands-on learning and do as habituation, very influential in improving the development of religious and moral values early childhood in RA (Kindergarten) Masyithoh Pabelan Semarang District.